(untitled) (Fiep Bulletin - online, 2013)
Identify the influences of the Capotherapy on the elderlies’ physical aspect in a Social Project of a Companionship Center in Dourados/MS while investigating the concept of Capotherapy among the sample and analyzing the physical influences provided by the practice of this modality of physical activity/exercise. The research inference was through a qualitative approach, with questions half-structured, with the population composed by 32 elderly people with ages between 60 to 93 of both genders. Most part of the interviewed affirmed to know capoeira only by performances, being that just one of them had already practiced and they ignored the term Capotherapy and its mean of practice adapted to any age or social level. After the intervention, all of them liked the activities offered by the capotherapy very much and they said to get an improvement on the physical aspect due to the dynamic applied. It can be concluded that the Capotherapy brought a large contribution on the improvement of the physical pains and consequent of the getting old process allied to the sedentarism, providing them physical welfare with the practice of physical activity well orientated, what makes believe even more in this method, that besides new, shows a positive result, according reports of interviewed people in this search.